Detect Determinants of Profitability Performance of Sharia Bank - Aprih Santoso (Relevance: Journal of Management and Business, 2020)
Abstract : This study is to examine: (1) Effect of Capital Adequacy Ratio (CAR) on Return On Assets (ROA). (2) Non Performing Financing (NPF) is it able to strengthen the relationship between Capital Adequacy Ratio (CAR) to Return On Assets (ROA). The sampling method used in this study is a census that is all Islamic banks registered at Bank Indonesia consistently in the 2013-2018 period that numbered 72 Islamic Banks. The results of this study show that: (1) Capital Adequacy Ratio (CAR) has a positive and significant effect on Return On Assets (ROA). (2) Non Performing Financing (NPF) significantly strengthens the positive relationship between Capital Adequacy Ratio (CAR) and Return on Assets (ROA).